UX Comparison of Physical Traces, Samsung Health, Strava with EUCS Method - Rini, Alefia; Shofiati, Ratna; Zuhdi, Ahmad (Intelmatics, 2026)
The development of digital technology has encouraged people to be more concerned about their health through the use of physical activity monitoring applications. This study aims to compare user experiences of three physical activity tracking applications, namely Physical Traces (developed by researchers), Samsung Health, and Strava, using the End User Computing Satisfaction (EUCS) approach. EUCS assesses user satisfaction based on five dimensions: content, accuracy, format, ease of use, and timeliness. Data were collected through a 4-point Likert scale-based questionnaire distributed to 107 respondents. The results showed that all questionnaire items were valid and reliable. The Samsung Health application excelled in the content and timeliness dimensions, Strava excelled in accuracy, while Physical Traces had the highest scores in ease of use and format. However, a statistically significant difference was found only in the accuracy dimension (p = 0.0016). These findings provide an overview of the strengths and weaknesses of each application, as well as input for improving the Physical Traces application in the future.